Serum levels of IL-6, TNF-α, and YKL-40 in patients with stage I multiple myeloma - Zeinab Esmaeilzadeh; Fatemeh Kheradmand; Yousef Rasmi; Mohammad Hassan Khadem-Ansari (Journal of Research in Applied and Basic Medical Sciences, 2020)
Background & Aims: Multiple myeloma (MM) is a type of plasma cell malformation accounting for 10% of the blood cancers with unknown ethiopathology. MM causes changes in inflammatory proteins. The aim of this study was to evaluate the serum levels of IL-6, TNF-α, and YKL-40 in patients with stage I MM. Materials & Methods: This case-control study was performed on 28 patients with stage I MM including 14 males and 14 females with mean age of 62.11 ± 6.71 years and 40 individuals as controls including 20 males and 20 females with mean age of 60.25 ± 4.81 years matched in both age and sex. Serum concentrations of inflammatory factors including IL-6, TNF-α and YKL-40 were measured using the sandwich Enzyme Linked Immunosorbent Assay (ELISA) method and the data were analyzed using SPSS software. Results: The serum levels of IL-6 in patients with stage I MM (7.42±5.89 pg/ml) were significantly higher compared to the control group (1.67±1.08 pg/ml); (p< 0.0001). Also, the serum levels of YKL-40 in the patients (45.86 ± 9.14 ng/ml) were significantly higher compared to the control group (35.87 ± 11.2 ng/ml); (p <0.0001). Also, the levels of TNF-α (8.02±1.75 pg/ml) were slightly high compared to the control group (7.77 ± 1.91 pg/ml); (p=0.419). Conclusion: According to the results in MM, inflammatory proteins such as YKL-40 andIL-6 are the major growth factor of the myeloma cells and help their survival.